Television as a Tool of Memory and Identity in Khaled Hosseini’s Novels - Priya Meena; Rajiv Ranjan Dwivedi (IAFOR Journal of Arts & Humanities, 2023)
Globalization epitomizes the convergence of diverse cultures, economies, and communities on a worldwide scale, engendering the exchange of ideas, technology, inventions, and import and export services across nations and societies. Technology, as a pivotal agent, assumes a vital role in building bridges among the global economies by overcoming information disparities and thereby empowering people. Specifically, television, a very influential medium, assumes the function of capturing, collating, and disseminating personal and cultural memories. Its significance is especially pronounced in the context of Khaled Hosseini’s literary works, The Kite Runner and A Thousand Splendid Suns, where television’s role as a tool for constructing memories and shaping the identities of the characters is scrutinized. The ramifications of the Taliban’s television ban are examined in this paper, highlighting how this drastic measure has significantly impacted the nation’s culture.